TRANSFORMING MARGINALIZED SOCIETY: SOCIAL ENTREPRENEURSHIP IN TODAY’S MALAYSIAN BUSINESS LANDSCAPE - Suresh Nodeson; Kesavan Nallaluthan, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Social entrepreneurship is becoming more widely acknowledged as crucial in tackling the most urgent social, environmental, and economic issues in the world. While existing reports on social entrepreneurship in Malaysia provide a broad overview, they often fail to capture the nuanced and dynamic growth of social enterprises serving the autism spectrum disorder community, where practical innovations and focused initiatives drive meaningful progress and provide crucial support for individuals and families. A qualitative study approach, using multiple case studies, has been used to explore and understand the phenomenon of social entrepreneurship in Malaysia by choosing six founders of social companies based in Klang Valley, Malaysia, to participate in this study. Data collection would be a face-to-face interview. Using thematic analysis, the researcher can identify these organizations' unique challenges and the targeted initiatives driving meaningful progress and providing crucial support for individuals and families. subsequently developing strategies to enhance the impact and sustainability of social enterprises in Malaysia.